Does IQ affect the functional brain network involved in pseudoword reading in students with reading disability? A magnetoencephalography study - Simos, Panagiotis G.; Fletcher, Jack M.; Rezaie, Roozbeh; Papanicolaou, Andrew C. (Frontiers in Human Neuroscience, 2014)
The study examined whether individual differences in performance and verbal IQ affect the profiles of reading-related regional brain activation in 127 students experiencing reading difficulties and typical readers. Using magnetoencephalography in a pseudoword read-aloud task, we compared brain activation profiles of students experiencing word-level reading difficulties who did (n=29) or did not (n=36) meet the IQ-reading achievement discrepancy criterion. Typical readers assigned to a lower-IQ (n=18) or a higher IQ (n=44) subgroup served as controls. Minimum norm estimates of regional cortical activity revealed that the degree of hypoactivation in the left superior temporal and supramarginal gyri in both RD subgroups was not affected by IQ. Moreover, IQ did not moderate the positive association between degree of activation in the left fusiform gyrus and phonological decoding ability. We did find, however, that the hypoactivation of the left pars opercularis in RD was restricted to lower-IQ participants. In accordance with previous morphometric and fMRI studies, degree of activity in inferior frontal and inferior parietal regions correlated with IQ across reading ability subgroups. Results are consistent with current views questioning the relevance of IQ measures and IQ-discrepancy criteria in the diagnosis of dyslexia.